Mapeamento geoestatístico tridimensional do teor de umidade e caracterização energética em pilhas de cavacos de madeira - Valentim, Larissa Benassi (2016)
The execution of this work aimed at the use of geostatistics to predict the spatial pattern of variation of moisture content in piles of eucalyptus wood chips intended for energy production to generate subsidies to adequate sampling and handling of the material. For this, piles wood chips were installed for evaluation in three different storage periods, these rings being made by the newly cut material in seven, thirty and sixty days of storage. Sampling occurred in both axial positions (top, middle and base) side, so that all samples were georeferenced in relation to the distance from the ground and the center of the pile. The moisture content of the wood chips in each sample point was determined by gravimetric method recommended by NBR 14929 (ABNT, 2003). In addition, samples were subjected to analysis bulk density, particle size distribution, chemical analysis and determination of its calorific value, aiming at energy material characterization. The humidity values were submitted to geostatistical analysis and kriging. Our results confirmed the spatial dependence of the moisture content over the piles stored at seven and thirty days, confirming that the use of geostatistics is a useful tool to support the creation of sampling protocols and assist moisture content distribution studies over the pile. The effect of rain was crucial to reduce the spatial dependence on pile sixty days of storage, indicating that the wood chips stored in the form of piles are subject to wetting even in inner parts of the pile. In general, Eucalyptus grandis wood chips showed satisfactory technological characteristics for energy production.